2019
DOI: 10.1007/s11356-019-05379-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of metal (loid) contaminated solutions using iron-peat as sorbent: is landfilling a suitable management option for the spent sorbent?

Abstract: This study firstly aimed to investigate the potential of simultaneous metal (loid) removal from metal (oid) solution through adsorption on iron-peat, where the sorbent was made from peat and Fe by-products. Up-flow columns filled with the prepared sorbent were used to treat water contaminated with As, Cu, Cr, and Zn. Peat effectively adsorbed Cr, Cu, and Zn, whereas approximately 50% of inlet As was detected in the eluent. Iron-sand was effective only for adsorbing As, but Cr, Cu, and Zn were poorly adsorbed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Based on the contaminant concentrations detected in the leachate, the waste can be deposited at landfills for (i) inert, (ii) non-hazardous or (iii) hazardous wastes. In previous studies (Kasiuliene et al 2019a , b ), it was concluded that the spent peat and iron–peat could not be landfilled at landfills for hazardous waste. The leaching of As, which intensified drastically under the reducing conditions, was one of the main factors hindering the landfilling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the contaminant concentrations detected in the leachate, the waste can be deposited at landfills for (i) inert, (ii) non-hazardous or (iii) hazardous wastes. In previous studies (Kasiuliene et al 2019a , b ), it was concluded that the spent peat and iron–peat could not be landfilled at landfills for hazardous waste. The leaching of As, which intensified drastically under the reducing conditions, was one of the main factors hindering the landfilling.…”
Section: Resultsmentioning
confidence: 99%
“…To tackle these issues, we combined two highly efficient sorbents, namely peat and Fe oxide, into one sorbent (iron–peat) that can simultaneously remove cationic (Cu, Zn) and anionic (As (arsenate, arsenite), Cr (chromate, dichromate)) contaminants from contaminated water (Kasiuliene et al 2018 ; Kasiuliene et al 2019a ). Thus, the amount of the resulting spent sorbent is lower in comparison with the case where several sorbents are used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peat also has a lot of functional groups, such as carboxyl, phenolic, hydroxyl, etc. (Figure 2a), which contributed significantly to the interactions with the positively charged heavy metal ions, and, consecutively, to its high adsorption capability [15,25,30]. Thus, the removal mechanism of peat is based upon metal biosorption, including chemisorption, complexation, adsorption on the surface, diffusion through pores, and ion exchange.…”
Section: Batch Experimentsmentioning
confidence: 99%